Analisis Kelayakan Ekonomi Pembangunan Jaringan Irigasi dengan Pertimbangan Ketidakpastian Biaya dan Suku Bunga - Minmahddun, Anafi (Unmuh Babel Press, 2025)
The development of irrigation networks is a strategic effort to enhance food security by increasing land productivity and farmers’ income. However, investment decisions for irrigation infrastructure require comprehensive economic feasibility evaluations to ensure that the resulting benefits outweigh the associated costs. This study aims to assess the economic feasibility of an irrigation network development project in Southeast Sulawesi by considering key investment indicators and future economic uncertainties. The analytical methods employed include the calculation of Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period over a 25-year project life cycle, as well as a sensitivity analysis by considering potential changes in investment cost and interest rate by ±25%. The results indicate that the irrigation development project is financially feasible, with an NPV of IDR 5,302.06 million, an IRR of 9% which exceeds the 6% discount rate, a BCR of 1.30, and a Payback Period achieved in the 15th year of operation. Sensitivity analysis confirms that the project remains feasible even under increased cost or interest rate scenarios; however, it is more sensitive to changes in construction cost. Therefore, the irrigation network project is not only economically viable under baseline conditions but also demonstrates strong resilience against economic uncertainties, making it a suitable priority for agricultural infrastructure development in the region.